Beyond the hype: unpacking the hidden challenges of nanofertilizers - Buthelezi, Nana Millicent Duduzile; Manganyi, Madira Coutlyne; Lebepe, Jeffrey (Frontiers in Environmental Science, 2025)
The application of nanotechnology in agriculture presents innovative solutions to improve crop production and food security, thus promoting sustainable practice. Nanofertilizers (NFs) derived from metal oxide nanoparticles (NPs) significantly improve soil quality by increasing the diversity and abundance of soil microbial communities, essential for nutrient cycling and soil health. They enhance nutrient uptake, stress resistance, and plant defense mechanisms leading to improved yield. The physical and chemical synthesis of NFs has a negative effect on the environment and human health due to the use of hazardous and toxic chemicals; thus, the green synthesis method is preferred as it is eco-friendly and cost effective. This work examines the evolving role of NFs in sustainable agricultural systems, exploring technological innovations, advantages, possible toxicity and limitations of NFs. It aims to provide a comprehensive overview of NFs’ potential to promote soil health, plant productivity and environmental sustainability, while presenting recommendations for future research trajectories.